Relationship of Arterial Changes in Acute Pancreatitis on CT Angiography with Modified CT Severity Index - Sanya Vermani; Aditya Kaushal; Arshpreet Kaur; Mohit Singla (Journal of Gastrointestinal and Abdominal Radiology, 2022)
Purpose To evaluate the prevalence of arterial changes in patients with acute pancreatitis (AP) on computed tomography angiography (CTA) and determine their association with etiology of AP, presence of necrosis, collections and severity of AP. Materials and Methods A total of 50 patients (20 women, 30 men; mean age: 43.04 ± 13.98; age range: 18–77 years) with AP underwent contrast-enhanced computed tomography (CECT) scan and CTA of abdomen, which was evaluated for necrosis and fluid collection (s). On CTA, splanchnic arterial structures were assessed for vascular complications. Association between vascular changes and presence of necrosis, fluid collections, etiology of AP and severity of AP (as assessed by modified computed tomography severity index CTSI) was determined. Results Arterial complications were seen in 28 percent (14/50). The most frequently involved artery was superior pancreaticoduodenal artery (12 percent), followed by splenic artery (8 percent) and right gastric artery (8 percent; Fig. 1). No significant association was seen between arterial changes and gallstone or alcohol-induced AP. Arterial changes showed a significant association with presence of acute necrotizing pancreatitis (ANP), presence of collections and severe AP (CTSI 8–10) (p < 0.05 for each). Conclusion Arterial changes on CTA are frequently seen in patients of AP having ANP. There is a significant association between arterial changes and presence of necrosis, collections and severe AP.